PENGARUH LIKUIDITAS TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Faizal Rizki Asmoro; Haryanto Haryanto (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of liquidity on stock returns in the Indonesian banking sector listed on the IDX during 2022–2024. Liquidity was measured using trading volume, market capitalization, book-to-market ratio, asset growth, and return on assets (ROA). Multiple regression analysis was employed with secondary data obtained from IDX and Bloomberg. A purposive sampling technique resulted in 46 banks with 101 valid observations after outlier elimination. The results indicate that ROA significantly and positively affects stock returns, while trading volume, market capitalization, book-to-market ratio, and asset growth show no significant effects. These findings highlight the importance of profitability as the main determinant of stock returns, providing implications for both investors and companies.